2020
DOI: 10.3390/f11090928
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Carbon Sequestration Costs for Pinus elliottii Afforestation Project of China Greenhouse Gases Voluntary Emission Reduction Program: A Case Study in Jiangxi Province

Abstract: Afforestation and reforestation (AR) is an important component of China’s Greenhouse Gases (GHG) Voluntary Emission Reduction Program, acting as a valuable nationwide carbon sink. Although a number of studies have explored the costs of creating a carbon sink, such an assessment is lacking for China’s GHG Voluntary Emissions Reduction Program. This study develops an economic carbon sink costs measurement model for the Pinus elliottii afforestation project, based on the land opportunity cost method, which incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Although the results of their research have a certain reference significance, they can hardly help to identify the occasions that different tree species and investment mode applied to reduce the cost. The current market price of carbon sink is 2.09-13.43 USD/t [6], which is much lower than calculated carbon sink costs in most cases, especially for PPP mode. This shows that PPP mode cannot effectively reduce carbon sink costs and attract enterprise investment at present in constructing NAPs of China.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although the results of their research have a certain reference significance, they can hardly help to identify the occasions that different tree species and investment mode applied to reduce the cost. The current market price of carbon sink is 2.09-13.43 USD/t [6], which is much lower than calculated carbon sink costs in most cases, especially for PPP mode. This shows that PPP mode cannot effectively reduce carbon sink costs and attract enterprise investment at present in constructing NAPs of China.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have indicated that forest trees generally absorb 1.83 tons of carbon dioxide and release 1.62 tons of oxygen per cubic meter of growth [5]. Compared with reducing greenhouse gas emissions, forest carbon sinks have obvious cost advantages [6]. At present, forests are regarded as not only an important ecosystem for our human beings, but also the major carbon sink pathway for mitigating climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to published research findings, the typical values for variables a, b, and c in certain humid continental monsoon climate regions of southern China, as stated in Eq. 3.12, are as follows (Jia et al, 2010;Cao et al, 2020)…”
Section: Modelling Of Fcsmentioning
confidence: 99%
“…ΔC CCER,t ΔC TREE PROJ,t C TREE PROJ,t2 − C TREE PROJ,t1 t 2 − t 1 , t 1 ≤ t ≤ t 2 (3.9)Furthermore, C TREE PROJ,t can be calculated as the product of biomass, carbon content rate, and the molecular weight fraction of C element in CO 2 , can illustrated asCao et al, 2020: …”
mentioning
confidence: 99%